Ta'u and Ofu/Olosega volcanoes: The “Twin Sisters” of Samoa, their P, T, X melting regime, and global implications - Stanley R. Hart; Matthew G. Jackson (Geochemistry, Geophysics, Geosystems, 2014)
Abstract The Samoan islands of Ta'u and Ofu/Olosega (Ofol hereafter) are single shield volcanoes that have erupted alkali basalt for the past 70 and 440 kyr, respectively. They are 20 km apart, and are the easternmost subaerial expressions of the Samoan plume. The isotopic data for these islands are published; we report here the first major and trace element data for Ofol. The two islands are similar isotopically and in trace elements. Their high 3He/4He marks them as being a FOZO mantle end‐member. By comparing data from both volcanoes, we test the efficacy of melting models in constraining the mantle compositions and their P‐T of melting. We show that the mantle sources are similar, with spidergrams that peak at Ta (4× BSE), and Lu ∼0.5× BSE. Melts and mantle sources both have Lu/Hf ratios that are too low to support measured 176Hf/177Hf ratios, pointing to a young enrichment event in the mantle source. Degrees of melting are 6.5% for Ta'u and 5.2% for Ofol. P‐T of melting show a wide, overlapping range, but define a precise array; average values are 1475°C—77 km for Ta'u and 1550°C—110 km for Ofol. The deepest P‐T estimate is 4.2 GPa and 1550°C. The P‐T array is either a melting adiabat, or a mixing line of melts equilibrated at various depths. Kinetic modeling shows melt re‐equilibration will be likely for ascent velocities (m/yr) less than 40/(conduit radius in cm)2. P‐T estimates for melting may typically be minimum values.